1994
DOI: 10.2223/jped.769
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding: how and why to promote it

Abstract: Amamentação: como e por que promover ResumoA promoção do aleitamento materno deve ser vista como uma ação prioritária para a melhoria da saúde e da qualidade de vida das crianças e de suas famílias. As estratégias de promoção da amamentação devem variar de acordo com a população, sua cultura, seus hábitos, suas crenças, sua posição sócio-econômica, entre outras características. No entanto, de fundamental importância em qualquer estratégia, é a conscientização da importância do aleitamento materno. Essa revisão… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
11

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 68 publications
0
4
0
11
Order By: Relevance
“…In this study, women who were not in union, particularly those who were formerly married were more likely to stop breastfeeding their infants than women who were in union. It has been suggested that the association between marital status and breastfeeding cessation may be due to the presence or absence of social, emotional and economic support of a partner [ 39 ]; however, these factors were not assessed in our study. A more plausible reason in Kenya, where HIV is high, is that a disproportionately large number of formerly married women are HIV positive and many women in this situation were until recently advised to exclusively breastfeed their infant for 6 months and then to rapidly wean [ 40 ].…”
Section: Discussionmentioning
confidence: 94%
“…In this study, women who were not in union, particularly those who were formerly married were more likely to stop breastfeeding their infants than women who were in union. It has been suggested that the association between marital status and breastfeeding cessation may be due to the presence or absence of social, emotional and economic support of a partner [ 39 ]; however, these factors were not assessed in our study. A more plausible reason in Kenya, where HIV is high, is that a disproportionately large number of formerly married women are HIV positive and many women in this situation were until recently advised to exclusively breastfeed their infant for 6 months and then to rapidly wean [ 40 ].…”
Section: Discussionmentioning
confidence: 94%
“…A plausible reason for this association may be due to the presence or absence of social, emotional and economic support of a partner. 41 Further, mothers with no formal education have been found to have higher odds of non-EBF compared with those who had secondary education or higher. 40 42 43 Our study found that the overall/pooled prevalence of PBF recorded in West and Central Africa was higher than the overall prevalence across all the 29 countries.…”
Section: Discussionmentioning
confidence: 97%
“…Não viver com o companheiro se associou a uma prevalência de aleitamento materno exclu-sivo 24% inferior. É importante que a mulher nutriz seja apoiada na prática da amamentação exclusiva por pessoas próximas, principalmente o companheiro, pois seu estímulo é o mais significativo para que a mulher possa amamentar 25 . De forma convergente ao presente estudo, Pereira et al 23 observaram que mulheres que viviam com Tabela 2.…”
Section: Discussionunclassified